Comparing phonological working memory in preschool children with and without stuttering - Ali Barikroo; Sayed Abolfazl Tohidast; Banafsheh Mansuri; Ghasem Yadegarfar (Vesnu Publications, 2011)
Background: One language-related area that has recently received more attention from researchers working in the field of stuttering is phonological working memory. The aim of the present study was to compare the phonological working memory abilities of normal children with those of children who stutter (CWS). Materials and Methods: 30 CWS aging 4-6 years were compared with their control counterparts in the same age range. Non-word immediate repetition task was used to measure reaction time and to study the effect of non-word length on the accuracy and verbal fluency of responses. The second task was non-word delayed repetition task which was applied to determine the speed and efficiency of learning non-words. Results: Between-group analysis showed significant differences for all of the indexes except accuracy of non-words. The mean of reaction times in CWS was significantly longer than that of the control group. Moreover, the rate of learning non-words in stutterers was slower than in the normal group and theses differences were significant. Furthermore, the analysis of response fluency on non-word repetitions across different non-word lengths in CWS showed that the percentage of disfluencies significantly increased along with an increase in nonword length. Although the percentage of correct non-words as a whole and across different lengths indicated that CWS produced slightly less correct non-words compared to the control group, this difference was not significant. Conclusion: The findings of the present study provides support for previous works, indicating that CWS's phonological working memory abilities lag to some degree behind that of normal children. Key words: Phonological Working Memory, Stuttering, Non-Word Repetition Task